Diferensiasi Otak Laki-laki dan Perempuan Guru Taman Kanak-kanak Aisyiyah Nyai Ahmad Dahlan Yogyakarta: Studi Pendidikan Islam Anak Usia Dini Perspektif Gender dan Neurosains - Suyadi Suyadi (Sawwa: Jurnal Studi Gender, 2018)
The male and female brains created by God are different. The existence of Islamic education specifically for men and women is a cultural construct. The existence of an attractive female-dominated teacher of Islamic Education Early Childhood (PIAUD) was investigated because it became a turning point in the formulation of gender studies between the emancipation of women and men. This study aims to explain the phenomenon of female teacher dominance in the perspective of gender and neuroscience. The research was conducted throughout 2017 at the TK Aisyiyah Nyai Ahmad Dahlan in Yogyakarta. This study used a qualitative approach, data collection techniques used observation, interviews, and documentation, while the triangulation analysis was carried out descriptively, comparatively and interpretatively. The results of the study showed that culturally sociological PIAUD teachers of TK Aisyiyah Nyai Ahmad Dahlan were 100% female. But this female dominance is not a gender bias because neuro-physiologically the corpus callosum and broca and wernicke's Area in the female brain is thicker and wider than the male brain. This condition makes female teachers able to educate children more empathic and communicatively than men.